2021
DOI: 10.1016/j.ijnurstu.2021.103901
|View full text |Cite
|
Sign up to set email alerts
|

Beyond ratios - flexible and resilient nurse staffing options to deliver cost-effective hospital care and address staff shortages: A simulation and economic modelling study

Abstract: Background In the face of pressure to contain costs and make best use of scarce nurses, flexible staff deployment (floating staff between units and temporary hires) guided by a patient classification system may appear an efficient approach to meeting variable demand for care in hospitals. Objectives We modelled the cost-effectiveness of different approaches to planning baseline numbers of nurses to roster on general medical/surgical units while using flexible staff to r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 33 publications
2
47
0
7
Order By: Relevance
“…The presented study shows that it will also be beneficial for the hospital’s financial performance. This is also confirmed by the latest analysis by Griffiths et al, who found that flexible and resilient nurse staffing options contribute to cost-effective hospital care and address staff shortages [ 34 ].…”
Section: Discussionsupporting
confidence: 59%
“…The presented study shows that it will also be beneficial for the hospital’s financial performance. This is also confirmed by the latest analysis by Griffiths et al, who found that flexible and resilient nurse staffing options contribute to cost-effective hospital care and address staff shortages [ 34 ].…”
Section: Discussionsupporting
confidence: 59%
“…We do not know the arguments for the variation in baseline rostering at the included EDs. Given that appropriate baseline staffing is necessary and higher baseline rosters have been shown to be more cost‐effective, this needs to be further elaborated and evaluated within the ED context (Emergency Nurses Association, 2018; Griffiths et al, 2021; Needleman et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…21,35 Needleman and a more recent paper by Griffiths et al both estimated that half the cost of improved staffing is offset by the saved costs from shorter LOS. 21,36 We used patients' total hospital LOS as an outcome with the rationale that while LOS may not capture specific patient outcomes (such as fall rate or infection rate), it represents a combined indicator of adverse patient outcomes and efficiency.…”
Section: Variablesmentioning
confidence: 99%